Gambaran kesiapan UMKM menuju industri halal Jawa Timur: An Overview of Small and Medium Enterprise (SME) Readiness towards The East Java Halal Industry - Abdoes Sjakoer, Nour Athiroh; Noerhayati, Eko; Mardiayani, Siti Asmaniyah; Said, M. Mas’ud (JURNAL AGROINDUSTRI HALAL, 2022)
East Java has tremendous potential as a center for an integrated Halal industry based on superior products/products/services. East Java also has halal-certified MSMEs, dominated by the food and beverage sector (mamin). So the purpose of this study is to examine the profile of food MSMEs and describe the level of readiness of food MSMEs related to the halal industry in East Java. Methods This research uses a blended method, namely quantitative descriptive and qualitative methods. The exploration method is through the Rapid Rural Appraisal (RRA). Response selection using a purposive sampling technique. The results of the descriptive analysis of the profile of MSMEs who became respondents in this study were that most MSMEs already had NIB and PIRT. Most MSMEs that have NIB also have PIRT (48.72%). Ownership of NIB and PIRT is a commitment of MSMEs to comply with the government’s business administration regulations. This shows the manager’s administrative order, which is the key in developing the halal industry and culture. In conclusion, SMEs with PIRT also have a halal policy, have attended halal training, and are orderly in selecting and taking an inventory of a well-organized list of materials, products, and equipment, inventory management, procedures, and traceability. However, in terms of product handling, internal audit, and administrative review, many people still use PIRT, even though they already use it. Therefore, the focus of support is on these issues.